Alloying with a few atomic percent of Ga makes MnAl thermodynamically stable. (15th April 2017) - Mix, T.; Bittner, F.; Müller, K.-H.; Schultz, L.; Woodcock, T.G.
Abstract: Ternary alloys of the form Mn55 Al45-x Gax have been produced in the range 0 < x < 45. In alloys with 5 < x ≤ 9 after appropriate heat treatments, two different phases with the L10 structure can be made to coexist. One is thermodynamically stable, as is binary MnGa, and the other is metastable, as is binary MnAl, but in the ternary alloys, both phases contain only a few atomic percent of Ga. The magnetic properties of the ternary alloys are superior to those of the binary analogues. The resistance to thermal decomposition of the ternary metastable phase is greatly improved compared to binary MnAl and the thermodynamically stable L10 phase does not undergo a phase transformation at temperatures up to at least 700 °C. These results enable longer processing times at higher temperatures thus facilitating the development of rare earth free MnAl-based magnets which are capable of providing a sustainable alternative to certain types of Nd-Fe-B. Graphical abstract: Image 1